Powdery mildew disease in sunflower : A review: POWDERY MILDEW DISEASE IN SUNFLOWER : A REVIEW - S CHANDER RAO; M SUJATHA; K KARUNA; K S VARAPRASAD (Journal of Oilseeds Research, 2015)
Sunflower (Helianthus annuus L.) is one of the most important oilseed crops in the world. It is introduced in India during seventies and has occupied an important position in the oilseed economy ofthe country. The area under sunflower has reached to a maximum of 2.5 million ha during 1994 which declined drastically within the last two decades to 6.9 lakh ha (2014-15). Among the production constraints, vulnerability of the released cultivars to diseases at both vegetative and flowering stages played a major role compelling farmers to switch over to alternate crops. Of the various diseases, alternaria leaf blight, downy mildew and sunflower necrosis diseases attack the crop during vegetative stage while powdery mildew infects the crop from flowering to post flowering and seed formation stages. Powdery mildew is the economically important disease of the tropical regions but has not been witnessed on sunflower in India till the recent past. In India, powdery mildew was reported in high intensity (80%) during the year 2006-07 on rabi crop in some areas around Bengaluru and Raichur which increased over the years. Currently, the disease is observed on the crop in all growing situations viz., kharif, rabi and spring recording 30-75 per cent disease severity and causing yield losses to the tune of 20-50 per cent necessitating research for development of management strategies. Intensive researchwork on sunflower powderymildewis being carried out at Indian Institute of Oilseeds Research, Hyderabad and University of Agricultural Sciences, Bengaluru and disease management practices are being worked out at various AICRP sunflower centres. This review presents the information on the distribution, economic importance, symptomatology, epidemiology, disease cycle, sources of resistance and management strategies for powdery mildew disease on sunflower.